2008
DOI: 10.1158/1078-0432.ccr-07-4636
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Toxicity and Efficacy of Trastuzumab Combined with Pertuzumab in Patients with Trastuzumab-Insensitive Human Epidermal Growth Factor Receptor 2–Positive Metastatic Breast Cancer

Abstract: Purpose:To evaluate safety and efficacy of trastuzumab with pertuzumab in patients with human epidermal growth factor receptor 2 (HER2)^positive metastatic breast cancer who had progressive disease on trastuzumab-based therapy. Experimental Design: Patients with measurable HER2 + metastatic breast cancer, V3 trastuzumab-based regimens, and left ventricular ejection fraction (LVEF) z55% received 8 or 6 mg/kg trastuzumab and 840 mg pertuzumab i.v. followed by 6 mg/kg trastuzumab and 420 mg pertuzumab every 3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 43 publications
1
94
1
1
Order By: Relevance
“…However, although such a therapeutic approach is not yet available for breast cancer, our data also suggest that a ''rechallenge'' with trastuzumab alone or in combination with another HER2-specific antibody like pertuzumab could be beneficial for the treatment of tumors that have initially shown a good response to the antibody and then relapsed. In fact, this is supported by recent clinical observations (49). Moreover, the fact that MCF7 cells maintained their level of HER2 expression despite the selection pressure exerted by trastuzumab and NK cells implicates that HER2 may be much more essential for mammary than for ovarian carcinoma cells-and thus be a much better target in breast cancer (which is again in line with the clinical reality).…”
Section: Discussionsupporting
confidence: 66%
“…However, although such a therapeutic approach is not yet available for breast cancer, our data also suggest that a ''rechallenge'' with trastuzumab alone or in combination with another HER2-specific antibody like pertuzumab could be beneficial for the treatment of tumors that have initially shown a good response to the antibody and then relapsed. In fact, this is supported by recent clinical observations (49). Moreover, the fact that MCF7 cells maintained their level of HER2 expression despite the selection pressure exerted by trastuzumab and NK cells implicates that HER2 may be much more essential for mammary than for ovarian carcinoma cells-and thus be a much better target in breast cancer (which is again in line with the clinical reality).…”
Section: Discussionsupporting
confidence: 66%
“…This was in contrast with findings from early clinical development, which suggested that pertuzumab might increase the cardiotoxicity of trastuzumab (15). Trials in neoadjuvant-and adjuvant-breast cancer will further clarify the cardiac risk in a treatment-naive, early breast cancer population.…”
Section: Discussioncontrasting
confidence: 61%
“…84 In another small phase II trial that combined trastuzumab with pertuzumab, 6 of 11 patients experienced a significant reduction in left ventricular ejection fraction, of which one was severe and induced congestive heart failure symptoms. 85 In summary, given the cardioprotective effects of paracrine NRG-1/ErbB signaling in the heart, therapies that block ErbB signaling may be expected to induce ventricular dysfunction. These effects should be pronounced in conditions in which the injured or overloaded heart has progressed into a state of "ErbB signaling dependency."…”
Section: Mechanisms Of Cardiotoxicity Of Targeted Erbb Therapy: What mentioning
confidence: 99%